2017
DOI: 10.3390/rel8040067
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Economic Inequality on Children’s Development and Achievement

Abstract: Abstract:Child poverty leads to many challenges at both societal and individual levels, and the two levels are interrelated. It is critical to recognize the complex implications of poverty, including short-term and long-term effects for children and families. After reviewing both the societal (e.g., economic costs, segregation, and unequal opportunity) and individual (e.g., effects on children's health, development, learning, and academic achievement) implications of poverty, this paper will describe a framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Similarly, Reardon (2011) and Walsh and Theodorakakis (2017) both discovered that income inequality has caused a growth in educational inequality. Growing poverty rates have led to the widening of the achievement between students of color and their peers.…”
Section: Findings/discussionmentioning
confidence: 98%
“…Similarly, Reardon (2011) and Walsh and Theodorakakis (2017) both discovered that income inequality has caused a growth in educational inequality. Growing poverty rates have led to the widening of the achievement between students of color and their peers.…”
Section: Findings/discussionmentioning
confidence: 98%
“…With half of the participants in the study by Knight and Perfect (2019) being Latinx, the researchers found that parental education and selfreported income were also significant contributors to academic performance. Given that these underrepresented populations experience significant health care disparities and educational inequities (Walsh & Theodorakakis, 2017), mindful inclusion of diverse samples representing students with all different cultural, racial/ ethnic, and socioeconomic backgrounds in future research is a mandate.…”
Section: Future Directionsmentioning
confidence: 99%
“…The children of poor households have less supportive networks and services available in their communities, witness higher rates of violent crime, have poorer nutrition, fewer recreational amenities, and a less healthy physical environment than children of affluence. Poor children have less access to quality childcare and early learning opportunities, all of which impact early brain development of children (Walsh and Theodorakakis , 49–50). During their primary education, the children of poor households are less ready for kindergarten, have lower proficiency in third grade reading, and attend schools with less spending per student that have higher chronic rates of absenteeism have a school culture with lower expectations of high school graduation and admission to college than their affluent peers.…”
Section: Economic Inequality and Equal Opportunitymentioning
confidence: 99%